Application of Next-Generation Sequencing in Infections After Allogeneic Haematopoietic Stem Cell Transplantation: A Retrospective Study - Zhang, Xiaoying; Li, Yun; Yin, Jin; Xi, Bixin; Wang, Na; Zhang, Yicheng (Frontiers in Cellular and Infection Microbiology, 2022)
A retrospective study aimed to determine the characteristics of infection and the diagnostic efficacy of next-generation sequencing (NGS) in patients with fever after allogeneic haematopoietic stem cell transplantation (allo-HSCT). A total of 71 patients with fever after HSCT were enrolled. Compared with conventional microbiological tests (CMTs), we found that the sensitivity of NGS versus CMT in the peripheral blood samples a was 91.2% vs. 41.2%, and NGS required significantly less time to identify the pathogens in both monomicrobial infections (p= 0.0185) and polymicrobial infections (p=0.0027). The diagnostic performance of NGS was not affected by the use of immunosuppression. What’s more, viruses were the most common pathogens of infections. These results indicated that the sensitivity, timeliness, and clinical significance of NGS were superior for detecting infection. While NGS has the advantage of identifying a wide range of potential pathogens, the positive rate is closely related to the sample type. Therefore, we suggest that in the clinical application of NGS to detect pathogens in paitents after allo-HSCT, the appropriate sample type and time should be selected and submitted to improve the positive rate and accuracy of NGS. NGS holds the promise of becoming a powerful technology for diagnosis of fever after HSCT.